ANÁLISE DO PROCESSO DE INUNDAÇÃO DA CIDADE DE RIO NEGRO/PR - Köene, Rafael (2013)
Floods, characterized by the overflowing waters of a river, are usually caused by excessive rainfall in a watershed. Floods in Brazil are frequent events which usually cause major damage when they reach cities and communities. The constraints of a flood are related to several factors, such as topography, climate, exceptional rains, use and occupation of the watershed, soil sealing and more. The municipality of Rio Negro, this research study area, located in the southeastern region of the state of Paraná. The urban area of Rio Negro stays near the right bank of the middle course of Rio Negro, affluent of the middle course of Rio Iguaçu, embraces a basin with over 9,000 km² located in the eastern portion of the border between the states of Paraná and Santa Catarina. As a result of the location of the city of Rio Negro near the river, the city historically has multiple records with different flood magnitudes. The objective of this study is to analyze the process of these floods in the city. The research was based on historical data consulted, books and old newspapers; historical series of rainfall and river stations, and topographic maps of the city of Rio Negro. According to historical data, the city of Rio Negro has record flooding since 1888, three years before the occurrence of a great flood which, as books and newspapers, have reached similar dimensions to flooding in 1983 and 1992, largest ever recorded in Rio Negro reaching more than 14 meters water depth. The time series provided data on rainfall in the watershed of Rio Negro and about quotas and flows of the Rio Negro in the namesake city. Were analyzed ten flood events in greater detail within the past 31 years, to establish some standards related to the process of flooding in the city. With regard to rainfall causing flooding, most are related to years of experience of El Niño and La Niña rains and that these are distributed differently by Rio Negro basin as the seasons with prolonged rains in summer and concentrated in winter. With the analysis of flow and average daily rainfall in the basin during the period defined as flooding process, it was possible to establish that, on average, with 280 mm rain in 15 days is enough to cause a flood in the city of Rio Negro and the rise time of Rio Negro flow is 1,5 times faster than the fall time of the waters to the average flow of the river. Based on topographical maps of the urban area of Rio Negro and the field work, we found that the city grew on the fluvial plain of Rio Negro and the largest floods have reached approximately 1000 urban lots and about 25% of the total area of Rio Negro.